Experimental liver models: From cell culture techniques to microfluidic organs‐on‐chip. (26th May 2021) - Polidoro, Michela Anna; Ferrari, Erika; Marzorati, Simona; Lleo, Ana; Rasponi, Marco
Abstract: The liver is one of the most studied organs of the human body owing to its central role in xenobiotic and drug metabolism. In recent decades, extensive research has aimed at developing in vitro liver models able to mimic liver functions to study pathophysiological clues in high‐throughput and reproducible environments. Two‐dimensional (2D) models have been widely used in screening potential toxic compounds but have failed to accurately reproduce the three‐dimensionality (3D) of the liver milieu . To overcome these limitations, improved 3D culture techniques have been developed to recapitulate the hepatic native microenvironment. These models focus on reproducing the liver architecture, representing both parenchymal and nonparenchymal cells, as well as cell interactions. More recently, Liver‐on‐Chip (LoC) models have been developed with the aim of providing physiological fluid flow and thus achieving essential hepatic functions. Given their unprecedented ability to recapitulate critical features of the liver cellular environments, LoC have been extensively adopted in pathophysiological modelling and currently represent a promising tool for tissue engineering and drug screening applications. In this review, we discuss the evolution of experimental liver models, from the ancient 2D hepatocyte models, widely used for liver toxicity screening, to 3D and LoC culture strategies adopted for mirroring a more physiological microenvironment for the study of liver diseases.